Analysis of speech acts in Charles Dickens' Great Expectations: A politeness language analysis - Arif Cahyono; Eka Fadilah; Lailatul Musyarofah (Jurnal CULTURE (Culture, Language, and Literature Review), 2023)
This research studies about politeness strategies in Charles Dickens Great Expectations. The writer analyze of Speech Acts in Charles Dickens' Great Expectations: A Politeness Language Analysis. The purposes of the research were to know the kinds of politeness strategies which used by the main characters in directive utterance and the politeness strategies of directive act in title. The data of this research was Charles Dickens' Great Expectations. This research was done by descriptive qualitative method. The research findings show that there were 2 types of politeness strategies. Based on the frequencies, the strategies applied in the data were Positive Politeness 145 frequencies (86%) and Negative Politeness 31 frequencies (14%). Based on the frequencies of directive utterance in the data were Pip 88 frequencies, Miss. Havisham 340 frequencies, Mrs. Joe Gargery 31 frequencies and Joe Gargery 8 frequencies.